Identification of genetic defects underlying FVII deficiency in 10 patients belonging to eight unrelated families of the North provinces from Tunisia - Elmahmoudi Hejer; Ben-lakhal Fatma; Elborji Wijden; Jlizi Asma; Zahra Kaouther; Sassi Rim; Zorgan Moez; Meddeb Balkis; Elgaaied Ben Ammar Amel; Gouider Emna (BMC, 2012)
Abstract Inherited factor VII (FVII) deficiency is a rare disorder characterized by a bleeding phenotype varying from mild to severe. To date, more than 200 mutations have been described along the F7 gene encoding for FVII. The aim of this study was the identification of genetic defects underlying FVII deficiency in 10 patients belonging to eight unrelated families of the North provinces from Tunisia. Mutation detection was performed by sequencing the whole F7 gene coding region, exon-intron boundaries and about 400 bp of the promoter region. We identified 5 mutations in five unrelated families; the novel p.F328Y mutation and the reported mutations: p.R304Q, p.M298I, IVS1aG > A and p.G-39G. For the remaining 5 patients we didn't identified any mutations using PCR/Sequencing protocol. In conclusion, this study represents the first comprehensive molecular series of FVII deficiency affected patients in Tunisia from the North. We will try in the future to continue the molecular study for Tunisian patients from Center and South provinces in order to have a complete idea about the FVII deficiency mutational profile in our country. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1288044089753085